Pyrazine-bridged Cu(ii) chains: diaquabis(n-methyl-2-pyridone)copper(ii) perchlorate complexes. Issue 39 (30th September 2020) - Kirkman-Davis, Emma; Witkos, Faith E.; Selmani, Veli; Monroe, Jeffrey C.; Landee, Christopher P.; Turnbull, Mark M.; Dawe, Louise N.; Polson, Matthew I. J.; Wikaira, Jan L.
Abstract : Reaction of pz, Cu(ClO4 )2 and n -Me-2(1 H )-pyridone (L) makes a family of S = ½, AFM chains [CuL2 (H2 O)2 pz](ClO4 )2 . The compounds were studied by crystallography, EPR and magnetic susceptibility showing a correlation with the Jahn–Teller axis. Abstract : A family of pyrazine-bridged, linear chain complexes of Cu(ii ) of the formula [CuL2 (H2 O)2 (pz)](ClO4 )2 [pz = pyrazine; L = n -methyl-2(1 H )-pyridone, n = 3 (1 ), 5 (2 ), and 6 (3 )] has been prepared. Single-crystal X-ray diffraction shows six-coordinate, pyrazine-bridged chains with trans-pairs of ancillary ligands. The substituted pyridine molecules exist in their pyridone tautomers and are coordinated through the carbonyl oxygen atom. The structure is stabilized by intramolecular hydrogen bonds between the pyridone and water molecule, and via hydrogen bonds between the water molecules and perchlorate ions. 2 undergoes a crystallographic phase transition between C 2/ c (high temperature phase) and P 1̄ (low temperature phase). Powder EPR spectra reveal that all complexes are rhombic, although differences between g x and g y can only be seen clearly at Q-band. Variable temperature magnetic susceptibility data show antiferromagnetic interactions and the data were fit to the uniform chain model yielding J / k B = −9.8, −9.2 and −11 K for 1–3 respectively. Attempts to model an interchain interaction strength indicate that the chains are very well isolated.